2022
DOI: 10.1111/trf.17159
|View full text |Cite
|
Sign up to set email alerts
|

The compound effect of irradiation and familial pseudohyperkalemia on potassium leak from red blood cells

Abstract: Background Familial pseudohyperkalemia (FP) is a rare asymptomatic condition characterized by an increased rate of potassium leak from red blood cells (RBC) on refrigeration. Gamma irradiation compromises RBC membrane integrity and accelerates potassium leakage. Here, we compared the effect of irradiation, applied early or late in storage, on FP versus non‐FP RBC. Study Design Five FP and 10 non‐FP individuals from the National Institute for Health Research Cambridge BioResource, UK, and three FP and six non‐F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…23,[35][36][37] It is also of interest because we have recently shown that irradiated RBCs have a very similar cation leak profile to FP RBCs. 14 Now, we show that cation-leaky RBCs (whether FP or irradiated) have very similar vesiculation profiles to each other and to control non-FP RBCs during cold-storage. It has been known for many years that irradiation increases the RBC plasma membrane permeability to cations 10 ; however, the membrane defect causing this permeability has not been determined.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…23,[35][36][37] It is also of interest because we have recently shown that irradiated RBCs have a very similar cation leak profile to FP RBCs. 14 Now, we show that cation-leaky RBCs (whether FP or irradiated) have very similar vesiculation profiles to each other and to control non-FP RBCs during cold-storage. It has been known for many years that irradiation increases the RBC plasma membrane permeability to cations 10 ; however, the membrane defect causing this permeability has not been determined.…”
Section: Discussionmentioning
confidence: 60%
“…As reported previously, 14 haemolysis was measured in the SN fraction, at all time-points +/À irradiation. Haemolysis increased with storage time but did not appear to be affected by irradiation (Supplemental Figure 2).…”
Section: Haemolysismentioning
confidence: 92%
See 3 more Smart Citations